Phosphate sources for acid soils in Vietnam - Nguyen Vy (Malaysian Society of Soil Science, 2013)
Agricultural production in Vietnam has made considerable progress in recent years. From a state when the country had to import food yearly, in 1989 Vietnam produced an amount of food, not only enough for self-sufficiency but also for export. Vietnam can achieve greater successes in agricultural production if phosphate fertilisers are available in greater quantities and used more judiciously. Phosphorus has now become the first limiting factor in increasing crop yield in Vietnam